Grundtvig teologiske udvikling til omkring affattelsen af »De levendes land« - Glenthøj, Elisabeth Albinus (Grundtvig-Studier, 1995)
The Development of Grundtvig ’s Theology until about the Time of the Composition of .The Land of the Living. About the Eschatological Tension in the Understanding of the Kingdom of God By Elisabeth Albinus Glenthøj In order to characterize briefly Grundtvig’s ideas about the Kingdom of God, the following statements are crucial: The Kingdom of God will break through visibly at the Second Coming of Christ. Until then the Kingdom is present to Faith and Hope through the Holy Spirit. The tension between the eschatological, visible Kingdom of God and the presence of the Kingdom now is a common theme in Grundtvig’s hymns. This study seeks to trace the development of Grundtvig’s theology towards his fully developed view of the Kingdom of God. The subject of the study is the great hymn, .The Land of the Living., from 1824, which contains beginnings of Grundtvig’s more elaborated view. The basic texts of the study are sermons by Grundtvig from 1821 to 1824, the period in which the eschatological tension emerges. Sections I to II.A. bring a chronological outline of the development of Grundtvig’s theology during the period until and including the year 1824. Section II.B. examines »The Land of the Living« in the light of this outline. Throughout the study the emphasis is on the emergence of the eschatological tension. From his parents Grundtvig inherits a belief in a Kingdom of God hereafter, but as Grundtvig experiences the presence of the Lord through the Holy Spirit - in his own life and in the Church - the theology develops towards an understanding of the Kingdom of God as already present to Faith and Hope through the Holy Spirit. The future visible Kingdom illuminates the life of the Church already. Thus the eschatological tension emerges. The continuity between the future and the present Kingdom of God is found in the union with Christ through the Holy Spirit. This union is granted in Baptism and is nourished first and foremost through the Eucharist, and, next, through prayer and words of praise. Grundtvig’s experience of Pentecost underlies »The Land of the Living«: The Holy Spirit builds up the heart of man to become a temple for the Father and Son (stanza 12). Stanzas 7 to 11 elaborate the content of this unity with the Trinity. From here originates the life of the Church in the love of God and of one’s neighbour, a life which, through the Holy Spirit, takes man closer to the likeness to Christ; the goal is reached in Eternity. Wherever the love of God prevails, the Kingdom of God is present (stanza 13); that is where men are »co-operating witnesses to the divine struggle of the Spirit against the flesh«, against everything »which seeks to ... wipe out His image, destroy His temple within us« (Eighth Sunday after Trinity, 1824).